Production of chicken sausage (Cobb 500 (Smith, 1992)): caracterisation of Physicochemical, microbiological and sensorial qualities.: Qualities of chicken sausage produced in Cameroon - Clotilde Ella, KAPCHE LEUNGUE; Christian, NDIH Aimé; Augustin, GOUDOUM; Aboubakar, Dr.; BOUBA Armand, ABDOU; Carl Moses, MBOFUNG (International Journal of Scientific Research and Management (IJSRM), 2018)
The aim of this work is to produce chicken sausage, hence, increasing the added value of chicken. The physicochemical and sensorial qualities were evaluated. Microbial quality was investigated during a period of one month under vacuum storage conditions at 4°C. From the results, it appears that the physicochemical parameters of chicken meat before processing and chicken sausage showed a significant (p